Tidal Dynamics and Climate Change in Coastal Waters of Pangkalan Sesai Village, West Dumai District, Riau Province - Febrian, Andi; Samiaji, Joko; Ghalib, Musrifin (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
The research was conducted from December 2014 to February 2015, in the coastal waters of Dumai, Riau Province. The research aimed to determine the tidal dynamics in relation to climate change. The research used survey method by performing 4 times periodically sampling. The result of measurement was then compared to Hydro-oceanographic Service Data.The results showed that tidal pattern in coastal waters of Dumai during a period of 3 months was classified into Mixed Semi-Diurnal Tides which occured 2 low tides and 2 high tides for 24 hours. Observations I-IV showed the tidal patterns were different because of different patterns of surface currents. Data of tidal pattern were compared to data obtained from Hydro-oceanographic data 3 years earlier showed a difference. Judging from the results of research that has been made known that there has been a rise in sea level if compared to data obtained from Hydro-oceanographic data 3 and 1 year before, namely an increase ranging between 19.5 to 22 cm. While the comparison of the data with the previous 2 years decreased, with a value of 45.5 cm. This means sea level in the study area has increased for 3 and 1 year. It was predicted that the existence of climate change has the effect of tidal conditions in these waters.Keyword : tidal pattern, climate change, Pangkalan Sesai, Dumai